(untitled) (Third Sector Social Economic Review, 2023)
This study deals with the silver economy strategy, which occurs as a natural result of the demographic transformation process and draws attention to the opportunities as well as the threats brought by the aging of the population, and the gerontechnology applications, which are a part of the silver economy. In the study carried out based on the literature review, it was concluded that the increasing fragility and need for care, especially in the older age groups, increased the need and demand for technology-supported products and services of elderly individuals and their families. However, it has been determined that there are various areas that need to be developed in line with the findings of existing studies and research in order to support the positive effects of gerontechnology applications on the welfare of the elderly. In this context, effective inclusion of individuals in the aging process in technology-supported innovation projects, taking into account the differences between the elderly age groups in the technology design processes, taking care that various types of gerontechnology applications do not reinforce negative stereotypes and age discrimination towards the elderly, and strengthening the interdisciplinary approach in the field of gerontechnology are important points to be noted. On the other hand, in order for the expected positive effects of gerontechnology applications to emerge in terms of elderly welfare, it is extremely important to provide public support that will enable poor elderly people to access relevant products and services, and to take into account the socio-economic and cultural differences of countries.